Pendidikan Kesehatan Mobilisasi Dini Pasca Bersalin - Isnaeni Rofiqoch; Purwati Purwati; Wulan Margiana (LPPM Akbid Harapan Ibu Pekalongan, 2020)
Health education is a process of providing knowledge and a process in public awareness of the importance of health. Health education on early mobilization for postpartum mothers can provide more knowledge about health to mothers or their families in order to overcome problems and accelerate the postpartum healing process. This is because the postpartum stage is one of the stages that is susceptible to bleeding and infection in the mother, and a cause of death in the mother. The method in implementing IbM is carried out by the method of learning by doing (learning by doing) with the transfer of knowledge through counseling, training and skill practice. In the implementation of providing health education about early mobilization after childbirth there is an increase in knowledge before and after providing health education about early mobilization after childbirth. Providing health education about early postpartum mobilization is carried out as early as possible, with the hope that post-partum mothers can immediately practice and help heal uterine wounds and postpartum birth canals.